VD_FINDINFO HC / 2011 / 283 vom 12. Mai 2011 - VD Tribunal cantonal (2011)
DIVORCE, MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, ENFANT | 137 al. 2 CC, 163 al. 1 CC, 176 al. 1 ch. 1 CC, 276 al. 1 CPC (CH), 317 al. 1 CPC (CH)